Art Drawing and Vegetable Planting on Auditory Hallucination Symptoms in Schizophrenia - Putri, Melsa Amanda; Warni, Hernida; Sari, Nova Nurwinda (Jurnal Ilmiah Kesehatan (JIKA), 2025)
Schizophrenia with auditory hallucinations is a serious mental health problem in Indonesia, affecting patients’ social functioning and quality of life. In 2024, the Aulia Rahma Foundation in Lampung recorded 117 patients, with 70% experiencing persistent auditory hallucinations despite receiving pharmacological therapy. This study aimed to examine the effectiveness of art drawing therapy compared to vegetable planting as a control group in reducing auditory hallucination symptoms. A quasi-experimental design with a nonequivalent control group design was used. The sample consisted of 38 schizophrenia patients with auditory hallucinations, selected through purposive sampling, and divided into an intervention group (art drawing therapy) and a control group (vegetable planting). Data were collected using the Auditory Hallucination Rating Scale (AHRS) and analyzed with paired t-test and independent t-test. The results showed a significant reduction in symptoms in both groups (p-value = 0,001 paired t-test; p-value = 0,004 independent t-test), with art drawing therapy demonstrating a greater decrease in symptoms compared to vegetable planting. In conclusion, both therapies are effective in managing auditory hallucinations in schizophrenia patients, with recommendations for developing a comprehensive occupational therapy program at the Aulia Rahma Foundation, focusing on art drawing therapy activities.